Factor affecting work-life balance among employees in Johor Bahru / Nurul Anis Faizah Mohamad Shah - Mohamad Shah, Nurul Anis Faizah (Faculty of Business and Management, 2018)
The purpose of this study is to determine the relationship between workload, organizational support and role conflict towards employees in Johor Bahru work-life balance. The study involves the problem on what factor that affecting work-life balance and whether the three independent variables is significant. The targeted population is local employees who are currently working in Johor Bahru and the sample in this study covered 310 respondents from the total population. The sample was selected through convenience sampling. From 310 questionnaire distributed, only 292 questionnaire were usable.